Emerging energetics alternatives - Bushnell, Dennis M (International Journal of Sustainable Energy and Environmental Research, 2024)
Energetics is the key to addressing climate change at scale and profitably. The current at scale and profitable climate energetics approach is renewables plus storage. This report summarizes nascent/emerging at scale and profitable energetics approaches for generation, storage, efficiency/conservation, and mitigation, the frontiers of responsible climate-related energetics. There are two weak nuclear force batteries that could provide competition for renewables and storage going forward. There are biologic approaches that could provide ultra-low-cost massive capacity biofuels, sequester massive amounts of atmospheric CO2, and increase the planet’s albedo. Based on the learnings from renewables, profitability is the apparent key to rapid, at scale response to climate change.